MOTIVASI KERJA KARYAWAN MELALUI EMPLOYEE RELATIONS - Melita, Yerah (Jurnal Insani, 2018)
One very important element to manage seriously is “Human” element. The human element or employee has an important role in a organization/ company, in addition to other elements such as: money, materials, methods, machinery, and market. It is important because employees are assets in an organization or company. Without employees, an organization/ company cannot operate.One way to motivate employees to be more enthusiastic in doing their work is employee relations activities. Through this activity the company can foster, establish and maintain a good or harmonious relationship between management and employees, and among employees.